2020
DOI: 10.1101/2020.05.10.086652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TDP-43 deficiency links Amyotrophic Lateral Sclerosis with R-loop homeostasis and R loop-mediated DNA damage

Abstract: TDP-43 is a DNA and RNA binding protein involved in RNA processing and with structural resemblance to heterogeneous ribonucleoproteins (hnRNPs), whose depletion sensitizes neurons to double strand DNA breaks (DSBs). Amyotrophic Lateral Sclerosis (ALS) is a neurodegenerative disorder, in which 97% of patients are familial and sporadic cases associated with TDP-43 proteinopathies and conditions clearing TDP-43 from the nucleus, but we know little about the molecular basis of the disease. Here, we prove that misl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Besides its RNA-regulatory roles, TDP-43 is also implicated in DNA damage repair. TDP-43 depletion causes an accumulation of DNA double-strand breaks (DSBs), while TDP-43 overexpression is protective against DSBs [16,[74][75][76][77]. TDP-43 is rapidly recruited at DSB sites upon induction of DNA damage to stably interact with factors regulating DNA damage response and non-homologous end joining [74,75].…”
Section: Nuclear Bodies (Nbs)mentioning
confidence: 99%
“…Besides its RNA-regulatory roles, TDP-43 is also implicated in DNA damage repair. TDP-43 depletion causes an accumulation of DNA double-strand breaks (DSBs), while TDP-43 overexpression is protective against DSBs [16,[74][75][76][77]. TDP-43 is rapidly recruited at DSB sites upon induction of DNA damage to stably interact with factors regulating DNA damage response and non-homologous end joining [74,75].…”
Section: Nuclear Bodies (Nbs)mentioning
confidence: 99%
“…Therefore, the results obtained in C2C12 suggest another possible mechanism on how TDP-43 may control gene expression in muscle in an indirect fashion and eventually participate in disease. Recently, loss of TDP-43 was associated with increased genomic instability and R-loop formation (Giannini et al, 2020;Wood et al, 2020) possibly through mechanisms involving Poldip3, which has been shown to play a role in maintaining genome stability and preventing R-loop accumulation at sites of active replication (Björkman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%